Risk factors for respiratory tract bacterial colonization in adults with neuromuscular or neurological disorders and chronic tracheostomy. (June 2019) - Lepainteur, Margaux; Ogna, Adam; Clair, Bernard; Dinh, Aurélien; Tarragon, Catherine; Prigent, Hélène; Davido, Benjamin; Barbot, Frédéric; Vaugier, Isabelle; Afif, Muriel; Roux, Anne-Laure; Rottman, Martin; et al.
Abstract: The aim of this study was to describe the endotracheal respiratory flora in a population of adults suffering from neuromuscular or neurological disorders requiring a long-term tracheostomy and to identify risk factors for colonization. We conducted a prospective and single-center observational study among patients with chronic tracheostomy admitted for planned respiratory assessment between February 2015 and December 2016. Data were collected from patient interview and medical charts with a standardized questionnaire. A tracheal aspiration was performed for each patient. Humidifiers were analysed for bacteriological contamination. Overall 77 tracheal aspirates (TA) were obtained from patients included. Pathogenic bacteria were found in 90% of cases (69/77) with a majority of Pseudomonas aeruginosa (32/77, 41%), Staphylococcus aureus (34/77, 44%) and Serratia marcesens. (22/79, 38%) Amoxicillin + Clavulanic-acid and Cefotaxime were adapted for respectively in only 28% and 35% of the subjects due to the natural resistance of organisms. No pathogenic bacteria were isolated from humidifier samples. Risk factors significantly associated with P. aeruginosa colonization were residence in a medical-care home (p = 0.01, OR = 3.8 [1.1; 15.1]) and the presence of a cuff (p = 0.003, OR = 4.4 [1.1; 20.6]). Significant quantities of pathogenic bacteria are frequently isolated from TA of tracheostomised patients in the absence of infection. The frequent resistance of these pathogens to Amoxicillin + Clavulanic-acid precludes the use of this antibiotic in the empiric treatment of pneumonia in this population. Highlights: Potentially pathogenic bacteria are present in 90% of TA from chronic tracheostomised subjects for neuromuscular or neurological disorder in the absence of any infectious episode. Pathogenic bacteria from the water predominate in TA suggesting contamination during care. P. aeruginosa are more frequently isolated in adults living in a medical-care home rather than at their own home, suggesting a higher pressure of selection or colonization. Empirical treatment of pneumonia with a broad-spectrum antibiotic such as piperacillin-tazobactam or levofloxacin must be used until microbiological confirmation.